Big government and affirmative action : the scandalous history of the Small Business Administration - Bean, Jonathan J. (The University Press of Kentucky, 2015)
David Stockman, Ronald Reagan's budget director, proclaimed the Small Business Administration a ""billion-dollar waste -- a rathole, "" and set out to abolish the agency. His scathing critique was but the latest attack on an agency better known as the ""Small Scandal Administration."" Loans to criminals, government contracts for minority ""fronts, "" the classification of American Motors as a small business, Whitewater, and other scandals -- the Small Business Administration has lurched from one embarrassment to another. Despite the scandals and the policy failures, the SBA thrives and small bus.